Battling the smoking epidemic: How Indonesia can boost its economy and health with proven global strategies - Fahlevi Mochammad; Razaki Wiky Fhalyang; Matroji Fajar Juanda; Dahlan Sahara Putri (E3S Web of Conferences)
The research aims to assess the impact of implementing the Framework Convention on Tobacco Control (FCTC) in Indonesia, which has one of the highest smoking rates worldwide. Utilizing a systematic literature review, the study analyzes global case studies and local tobacco control policies. The results suggest that the adoption of FCTC strategies, including raising tobacco taxes, enforcing comprehensive advertising bans, and establishing smoke-free environments, could significantly benefit public health and the economy. These benefits are evidenced by decreased healthcare expenses, reduced smoking rates, and enhanced economic productivity. Although there might be short-term economic challenges, the research supports that the long-term advantages of implementing the FCTC in Indonesia surpass these initial costs, making a strong argument for the adoption of these regulations.